Estimating Water Poverty in Small Cities in Nepal - Bista , Raghu (Economic Journal of Development Issues, 2024)
Nepal is water rich climate prone country where small cities are facing escalating water scarcity and stress at household levels, this study estimates water poverty in these small cities across different elevations in the water basin in Nepal and households’ imperative behaviors. Using cross-sectional data sets of water poverty collected from the 12 small cities of the water basin in Nepal in 2022, the study employs descriptive statistics and the water poverty estimation method. As a result, headcount poverty reveals extreme water poverty, with 63.7 percent of the population living below the minimum threshold of 20 liters per capita per day and 95.82 percent below the maximum threshold of 50 liters per capita per day, despite the purported availability of water.Ecologically, there is less water poverty in the hills in the Terai and Himalayas at the minimum threshold, while it is uniform across all regions at the maximum. The levels of water poverty in cities vary widely. The cities of Devighat, Dordi, Besishar, and Abhukharini have the lowest levels of water poverty, while all small cities have at least 50 percent water poverty. This highlights the significant disparity between the supply and demand of water. Physical infrastructure and the economic capacity of people and cities to afford and access safe drinking water have identified constraints. Otherwise, climate change has stressed water availability. These results reveal the negative implications of climate change, water stress, and water poverty. This study provides a predictability of future complications in water stress and poverty at the household level. Therefore, it would be a valuable input to the water management system and preparedness for water. Further, it would extend to point out infrastructure constraints and households’ adaptation capacity and behavior.